دور المدرسة في تعزيز الهوية الثقافية الوطنية في ظل العولمة : دراسة ميدانية في ثانويات مدينة بئر العاتر - معيفي بوبكر (University Eloued جامعة الوادي, 2024)
تهدف هذه الدراسة إلى التعرف على دور المدرسة الجزائرية في ترسيخ قيم الهوية الثقافية في نفوس التلاميذ, ودور الأستاذ في مساعدتهم على التمسك بهويتهم والمحافظة على اللغة العربية والدين الإسلامي والموروث الثقافي, وكيفية الاستفادة من العولمة في جانبها الإيجابي, وتحديد مفهوم الهوية الثقافية الوطنية في المدرسة الجزائرية. وانطلقت الدراسة من التساؤل التالي: - ما أهمية الدور الذي تلعبه مؤسسات التعليم الثانوي في تعزيز الهوية الثقافية الوطنية في ظل العولمة؟ وللإجابة على هذا التساؤل طرحنا أربعة فرضيات وهي كالآتي: - يساهم التفاعل الاجتماعي في مؤسسات التعليم الثانوي في المحافظة على مهارات اللغة العربية لدى التلاميذ. - لمؤسسات التعليم الثانوي دور في نقل وترسيخ التراث الثقافي الجزائري للتلاميذ في ظل تحديات العولمة. - تساهم مؤسسات التعليم الثانوي في تعزيز قيم المواطنة لدى التلاميذ في مواجهة العولمة. - لمؤسسات التعليم الثانوي دور في غرس قيم الدين الإسلامي وتعزيزها في نفوس التلاميذ في ظل تحديات العولمة. وقد اعتمدنا على المنهج الوصفي بطريقة المسح الشامل نظرا لمناسبته للبحث الذي تمثل مجتمعه في سبعون أستاذ ثانوي يتوزعون على سبعة ثانويات, وبعد أن قمنا بعرض الأدبيات حول متغيرات الدراسة المتمثلة في المدرسة والهوية الثقافية والعولمة, قمنا بتحليل البيانات اعتماد على برنامج (SPSS) باستخدام التكرارات والنسب المئوية والمتوسط الحسابي العام للتكرارات, ومن خلال التحليل الكمي للبيانات توصلنا إلى النتائج التالية: - يساهم التفاعل الاجتماعي داخل الوسط المدرسي في المحافظة على اللغة العربية. - تقوم مؤسسات التعليم الثانوي بنقل وترسيخ التراث الثقافي الجزائري للتلاميذ. - تقوم مؤسسات التعليم الثانوي بتعزيز قيم المواطنة في نفوس التلاميذ. - تقوم مؤسسات التعليم الثانوي بدورها في غرس قيم الدين الإسلامي وتعزيزها في نفوس التلاميذ. Abstract This study aims to identify the role of the Algerian school in instilling the values of cultural identity in the students, and the role of the teacher in helping them attach to their identity and preserve the Arabic language, the Islamic religion and cultural heritage, as well as how to benefit from the positive aspect of globalization , and to define the concept of national cultural identity in the Algerian school. . The study started from the following question: - What is the importance of the role played by secondary schools in strengthening national and cultural identity in light of globalization? To answer this question, we put forward four hypotheses: - Social interaction in secondary schools contributes to maintaining students’ Arabic language skills. - Secondary schools have a role in transmitting and consolidating the Algerian cultural heritage in students in light of the challenges of globalization. - Secondary schools contribute to strengthening the values of citizenship among students in the face of globalization. Secondary schools have a role in instilling and strengthening the values of the Islamic religion in Algerian students in light of the challenges of globalization. We opted for the descriptive approach in the form of a comprehensive survey because of its suitability for research whose population was represented by seventy secondary school teachers practicing in seven high schools. After we presented the literature on the variables of the study about school, cultural identity, and globalization, we analyzed the data based on a program (SPSS) using frequencies, percentages, and arithmetic mean. General frequency, and through quantitative analysis of the data, we had the following results: - Social interaction within the school environment contributes to the preservation of the Arabic language. - Secondary schools transmit and consolidate the Algerian cultural heritage in students. - they strengthen the values of citizenship in the students. - they also play their role in instilling and strengthening the values of the Islamic religion in the hearts of students.
أطروحة
Keywords: المدرسة; العولمة; الهوية; الثقافة; التعليم الثانوي; the school; Globalisation; identity; the culture; high school